Agronomic Practices to Increase the Yield and Quality of Common Bean (Phaseolus vulgaris L.): A Systematic Review - Ioannis Karavidas; Georgia Ntatsi; Vasiliki Vougeleka; Anestis Karkanis; Theodora Ntanasi; Costas Saitanis; Evgenios Agathokleous; Andreas Ropokis; Leo Sabatino; Fanny Tran; Pietro P. M. Iannetta; Dimitrios Savvas (Agronomy, 2022)
Common bean (Phaseolus vulgaris L.) is the most important legume for human consumption worldwide and an important source of vegetable protein, minerals, antioxidants, and bioactive compounds. The N2-fixation capacity of this crop reduces its demand for synthetic N fertilizer application to increase yield and quality. Fertilization, yield, and quality of common bean may be optimised by several other agronomic practices such as irrigation, rhizobia application, sowing density, etc. Taking this into consideration, a systematic review integrated with a bibliometric analysis of several agronomic practices that increase common bean yield and quality was conducted, based on the literature published during 1971–2021. A total of 250 publications were found dealing with breeding (n = 61), sowing density and season (n = 14), irrigation (n = 36), fertilization (n = 27), intercropping (n = 12), soilless culture (n = 5), tillage (n = 7), rhizobia application (n = 36), biostimulant/biofertilizer application (n = 21), disease management (n = 15), pest management (n = 2) and weed management (n = 14). The leading research production sites were Asia and South America, whereas from the Australian continent, only four papers were identified as relevant. The keyword co-occurrence network analyses revealed that the main topics addressed in relation to common bean yield in the scientific literature related to that of “pod”, “grain”, “growth”, “cultivar” and “genotype”, followed by “soil”, “nitrogen”, “inoculation”, “rhizobia”, “environment”, and “irrigation”. Limited international collaboration among scientists was found, and most reported research was from Brazil. Moreover, there is a complete lack in interdisciplinary interactions. Breeding for increased yield and selection of genotypes adapted to semi-arid environmental conditions combined with the suitable sowing densities are important agronomic practices affecting productivity of common bean. Application of fertilizers and irrigation practices adjusted to the needs of the plants according to the developmental stage and selection of the appropriate tillage system are also of high importance to increase common bean yield and yield qualities. Reducing N-fertilization via improved N-fixation through rhizobia inoculation and/or biostimulants application appeared as a main consideration to optimise crop performance and sustainable management of this crop. Disease and weed management practices appear neglected areas of research attention, including integrated pest management.